Determination of N-Nitrosamines by Gas Chromatography Coupled to Quadrupole–Time-of-Flight Mass Spectrometry in Water Samples - Benigno José Sieira; Inmaculada Carpinteiro; Rosario Rodil; José Benito Quintana; Rafael Cela (Separations, 2020)
An analytical method based on high-resolution quadrupole−time-of-flight (QToF) mass spectrometry has been developed as an alternative to the classical method, using a low-resolution ion trap (IT) analyzer to reduce interferences in N-nitrosamines determination. Extraction of the targeted compounds was performed by solid-phase extraction (SPE) following the United States Environmental Protection Agency (USEPA) -521 method. First, both electron impact (EI) and positive chemical ionization (PCI) using methane as ionization gas were compared, along with IT and QToF detection. Then, parameters such as limits of detection (LOD) and quantification (LOQ), linearity, and repeatability were assessed. The results showed that the QToF mass analyzer combined with PCI was the best system for the determination of the N-nitrosamines, with instrumental LOD and LOQ in the ranges of 0.2−4 and 0.6−11 ng mL−1, respectively, which translated into method LOD and LOQ in the ranges of 0.2−1.3 and 0.6−3.9 ng L−1, respectively. The analysis of real samples showed the presence of 6 of the N-nitrosamines in influent, effluent, and tap water. N-nitrosodimethylamine (NDMA) was quantified in all the analyzed samples at concentrations between 1 and 27 ng L−1. Moreover, four additional nitrosamines were found in tap and wastewater samples.